PARAMETERS OF CARDIORESPIRATORY SYNCHRONISM AND THEIR DERIVATIVES IN THE ASSESSMENT OF THE FUNCTIONAL STATE WHEN RESTORING ERECTILE FUNCTION IN MEN AFTER PROSTATE CANCER TREATMENT METHOD HIFU - A. G. PENZHOYAN (Кубанский научный медицинский вестник, 2018)
Aim. To assess the functional state in the recovery of erectile function in men after the treatment of cancer by HIFU, the parameters of cardiopulmonary synchronism and their derivatives.Materials and methods. Observations were performed on 24 patients aged 45-56 years, who were referred to the increase in the level of the prostatic specific antigen for inpatient treatment in the urological department. At their inspection the cancer of a prostate of I-II stage has been diagnosed. Patients underwent a cardiac-respiratory synchronism test and determined the regulatory-adaptive status index and regulatory-adaptive capabilities by its parameters. After diagnosis, patients were assigned tumor destruction by transrectal high-intensity focused ultrasound ablation. After the operation, the patients were discharged from the hospital the next day and further follow-up was conducted in an outpatient setting with a visit to the hospital at 1, 3, 6, 12 months. After 6 months, the sample of the cardiopulmonary synchronism was repeated. According to questionnaires subjective assessment of the international index of erectile function ICEF-5, the QOL index assessment of quality of life. Statistical analysis of the results of the study was carried out using the programs: "STATISTIKA 6.0 for Windows". After establishing the normal distribution of the variant, significant differences were used in comparing the mean values in paired comparisons, taking the t-test of Student for p <0,05.Results. Before treatment in a group of 24 patients, regulatory-adaptive capabilities were assessed as satisfactory. After treatment of prostate cancer with the method of transrectal high-intensity focused ultrasound ablation, the level of the prostatic specific antigen was sharply reduced from 6,81±0,32 to 0,70±0,01 ng/ml (p<0,001), the tumor volume from 39,8±0,4 to 8,5±0,3 cm3 (p<0,001). Six months after the treatment of prostate cancer, the synchronization range increased by 22,5%. The duration of synchronization development decreased by 39,1%. This led to an increase in the regulatory-adaptive status index by 100,6%. Regulatory adaptive capabilities varied from "satisfactory" to "good". Six months after the treatment of prostate cancer in patients, part of the prostate gland was preserved and ejaculation was possible. Erectile function resumed 6 months after surgery, when regulatory and adaptive capacities were restored. And in 16 people, whose index of regulatory-adaptive status was 77,9±0,4, the international index of erectile function was 23,8±0,1 points. This indicates that the state of erection is normal. The index of quality of life assessment QOL they had 0,9±0,1 points, which corresponds to a good quality of life. In 8 patients with a regulatory-adaptive status index of 44,6±0,4, the international index of erectile function was 18,2±0,3, indicating mild erectile dysfunction. The index of QOL quality of life was 2,1±0,2 points, which corresponds to a satisfactory quality of life.Conclusion. The positive dynamics of the range of cardiopulmonary synchronism, a decrease in the duration of synchronization at the minimal border, an increase in the index of regulatory-adaptive status and regulatory-adaptive capabilities integrally reflect the consequences of effective treatment of prostate cancer and, consequently, the preservation of erectile function.